The effect of bipolar and monopolar resectoscope use on optic nerve diameter in transurethral resection of the prostate (Annals of Medical Research, 2022)
Aim: The aim of this study was to investigate the effects of monopolar and bipolar techniques of TURP under spinal anesthesia on serum electrolytes and changes in hemodynamic parameters, and to determine intracranial pressure changes by measuring optic nerve diameter with ultrasonography.Material and Method: Eighty ASA II-III patients who included in the study. The patients were divided into two groups as the monopolar and bipolar according to the resectoscope technique used by the surgeon. All patients underwent surgery under spinal anesthesia. Optic nerve sheath diameter was measured with ultrasound and the levels of Na+, K+, Hb were measured before and after the operation. In addition, the mean arterial pressure, heart rate and peripheral oxygen saturation of the patients were recorded at regular time intervals, and the amount of irrigation solutions used, the amount of intravenous volume administered and duration of operation were recorded.Results: In this study including 80 patients, the MAP and heart rate of patients at all perioperative time points and postoperative measurements were significantly lower when compared to baseline values (p
Keywords: TUR-P; optic nerve diameter; hyponatremia; spinal anesthesia